Yoga com educadores : estabelecendo caminhos rumo ao self e ao samadhi - Gelain, Denise (2008)
This research was characterised as a qualitative approach study under a comprehensive-interpretative perspective. Its purpose was to propose to educators the study of yoga through the koshas, in order to enable them to experience aspects related to the bodymind-spirit integration and to their real Self. The research has developed from the questioning about the meanings of the experiences with yoga with educators from the Associação de Pais e Amigos dos Excepcionais APAE( Down Syndrome Parents and Friends Association). The main theoretical reference were the espiritualistic theories of education, which bring in their essence the inventive and the symbiotic and synergic paradigms, that allege a tuning with all that exists, covering body-mind-spirit, as a portkey to the re-ligare, through the return to the union with the cosmos, with the divine, and with one´s very own essence. The information provided by the participants was collected during the experiences of yoga (asanas, pranayamas, mudras and yoga nidra) involving the study of koshas (levels of consciousness) through comments, questions and, in the last meeting, challenges proposed through the drawing of mandalas, the chosen language for the expression of the produced meanings. To interpret the images, the Leitura Transtextual Singular (Singular Transtextual Reading), developed by Ormezzano (2001) was used. The results showed that yoga awakened in the educators the need for personal revision of meaning and greater familiarity with their spiritual essence, combined to the other dimensions potentialized in the experiences. From this perspective, the use of yoga life philosophy with educators could be understood as a bold and challenging guideline, but relevant to the execution of a process to develop those human beings in all aspects, in their multiple dimensions so that, this way, they can live in a balanced and harmonious way with the true meaning of existence